Public debt relief for developing countries - Horst H. Gebauer (Intereconomics, 1978)
The problem of the growing indebtedness of developing countries is playing an increasingly important role at international conferences. It was also the central subject of the ninth special session of the UNCTAD Board whose third part ended on March 11, 1978. The resulting resolution, though not generally solving the debt problem, provides substantial progress for the poorer developing countries.
Keywords: 330; UNCTAD